Climate Action for Peace, Relief, and Recovery: Uniting Efforts at COP29 - Schapendonk, Frans; Rabie, Sara (2024)
COP29 Reflections by Frans Schapendonk, CGIAR Climate, Peace, and Security Specialist with the FOCUS Climate Security team at the Alliance of Bioversity and CIAT and Sara Rabie, CGIAR Climate, Peace, and Security Specialist with the FOCUS Climate Security team at the Alliance of Bioversity and CIAT.